Топонимическая лексика в довоенный период творчества Александра Трифоновича Твардовского - Koroleva, Inna (Acta Polono-Ruthenica, 2018)
The pre-war period (1926–1940) of A.T. Tvaedovskiy’s creative work, the great poet of the 20yh century, born in the Smolensk Region, is a period of his rising as an insuperable master of word, a people’s tribune, the time when the main traits of his poetry were developed and when his formation as a founder of the Smolensk Poetic School occurred. One of the central themes of the SPS poets, and first of all, A.T. Tvardovskiy himself, was the theme of “the minor” and “the big”. Motherland, which was materialized in significant motives through a system of toponyms. i.e. the names of geograpphical places. The article analyzes a system of macro- and mictrotoponyms and demonstrates their part in revealing of the thematical content of numerous pre-war poems (A Trip to Zagorye, 1939, Station Pochinok, 1936, and others), as well the first epical poem of the author Strana Muraviya (1936).